Implementasi Self-Tuning Pada Database Dengan Menggunakan Metode Nesterov Accelerated Gradient - Arif Rahmanto; Agung Setia Budi; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Tuning is the process of improving the performance of the database to achieve specific goals.. With the tuning process that is usually done by a database administrator still manually, the more time it takes for the database to be ready for use. For this reason, a system is designed to perform the automatic tuning of the database using the Nesterov accelerated gradient algorithm to change the value of the parameters that can improve database performance. The system is implemented in MariaDB database as the main database. Tests are carried out to change the previously set parameter values and the optimal parameter values are obtained after the 7th iteration. When testing the performance of the database with a large load, the database is able to significantly reduce the query time between before and after tuning. In the query load data of 1,000,000 database rows, there is a difference in the average execution time between before and after tuning with the Nesterov accelerated gradient algorithm of 1 minute 35 seconds. Whereas in the query load data 1,500,000 Row the average decrease in execution time is 14 minutes 26 seconds. From the test, it can also be concluded that the execution time is stable after the tuning process is carried out with the Nesterov Accelerated Gradient with the required execution time ranging from 24-45 seconds on testing load data of 1,000,000 rows and 75-120 seconds on testing load data of 1,500,000 rows.